An investigation of incurred human urine sample reanalysis failure. (May 2011) - Fu, Yunlin; Li, Wenkui; Smith, Harold T; Tse, Francis LS
Background: In this case study, urine samples were collected and transferred before the presence of a small degree of nonspecific binding was identified for the analyte of interest in human urine. The approach taken to address the issue was to use standards and quality controls to mimic the study samples and use Tween-80 (0.5%) to retrieve the adsorbed analyte. The method was validated, however, the incurred sample reanalysis (ISR) failed.Results: Investigation into the ISR failure unveiled ineffective mixing of the study samples, with almost no headspace left inside the sample tubes after the addition of the surfactant using a regular vortex mixer, as the cause of the ISR failure. All samples were reanalyzed using a modified sample mixing method, which resulted in two successful ISR runs.Conclusions: Thorough sample mixing after the addition of surfactant is one of the important steps in ensuring accurate and reproducible analyses of urine samples with a small degree of analyte nonspecific binding.